Staphylococcal proliferation and biofilm formation in vitro under the influence of cell-free extracts of probiotic origin - O. V. Knysh; O. Yu. Isaienko; Ye. M. Babych; M. M. Popov (Zaporožskij Medicinskij Žurnal)
Abstract The paper presents the results of the study on proliferation and biofilm formation by Staphylococcus aureus and Staphylococcus epidermidis under the influence of cell-free extracts obtained by the author’s method and containing derivatives of probiotic strains Вifidobacterium bifidum and Lactobacillus reuteri.